2008
DOI: 10.1016/j.jenvrad.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Role and influence of mycorrhizal fungi on radiocesium accumulation by plants

Abstract: This review summarizes current knowledge on the contribution of mycorrhizal fungi to radiocesium immobilization and plant accumulation. These root symbionts develop extended hyphae in soils and readily contribute to the soil-to-plant transfer of some nutrients. Available data show that ecto-mycorrhizal (ECM) fungi can accumulate high concentration of radiocesium in their extraradical phase while radiocesium uptake and accumulation by arbuscular mycorrhizal (AM) fungi is limited. Yet, both ECM and AM fungi can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 147 publications
1
21
0
Order By: Relevance
“…Declerck et al demonstrated that the extraradical hyphal network of AMF incorporate and translocate radiocaesium from a radiocaesium labelled root-free compartment to a root compartment, using a monoxenic multicompartment growing system 18 . De Boulois et al suggested that there was the possibility, although limited, of radiocaesium accumulation in the intraradical mycelium 19 . Chen et al also reported that AMF raised the biomass of Pteris vittata, significantly, when increased U concentrations in the root, and had a high transfer factor value, indicating that the intraradical hyphae may take advantage of microorganisms and rhizosphere microenvironment to transform radionuclides in soil effectively 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Declerck et al demonstrated that the extraradical hyphal network of AMF incorporate and translocate radiocaesium from a radiocaesium labelled root-free compartment to a root compartment, using a monoxenic multicompartment growing system 18 . De Boulois et al suggested that there was the possibility, although limited, of radiocaesium accumulation in the intraradical mycelium 19 . Chen et al also reported that AMF raised the biomass of Pteris vittata, significantly, when increased U concentrations in the root, and had a high transfer factor value, indicating that the intraradical hyphae may take advantage of microorganisms and rhizosphere microenvironment to transform radionuclides in soil effectively 20 .…”
Section: Introductionmentioning
confidence: 99%
“…These authors investigated whether the extraradical mycelium of Glomus intraradices (MUCL 41833) could take up U and translocate it towards its host. The experimental system selected for this first study was an in vitro bi-compartmented culture system (Dupré de Boulois et al, 2008;Declerck et al, 2005). Briefly, this system allows the culture of root organs in association with an AM fungus under monoxenic culture conditions and permits transport studies where only the fungal partner has access to a compartment containing a radio-tracer (Rufyikiri et al, 2005).…”
Section: Effect Of Phmentioning
confidence: 99%
“…Rufyikiri et al (2002) therefore suggested that polyphosphates could play a major role in the immobilization of U by G. intraradices. However, it should be pointed out that polyphosphates are not immobile, as they are involved in the translocation of P, and probably other elements from the extraradical hyphae to the intraradical structures of AM fungi (see Dupré de Boulois et al, 2008). Nonetheless, if we suppose that polyphosphates participate in the immobilization of U in the extraradical mycelium, it should be noticed that the pH of the cytoplasm, and of organelles of AM fungal mycelium is probably stable due to close metabolic control as it can be observed for any organisms or cellular compartment (Ayling et al, 1997;Kurkdjian and Guern, 1989).…”
Section: Effect Of Phmentioning
confidence: 99%
“…The behavior and transport of radionuclides in soil, plants and mushrooms have been the object of many investigations (Malinowska et al, 2006;Kaduka et al, 2006;Bazała et al, 2008;Bystrzejewska-Piotrowska and Bazała, 2008;Dupré de Boulois et al, 2008;Mietelski et al, 2010). The main factors controlling the 137 Cs levels in mushrooms are mycelium depth and ecophysiological behavior of fungi.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the dynamic of radionuclides in soils depends not only on their physicchemical interactions with inorganic and organic soil constituents, but also on biological interaction associated, to a large extent, with the microbial activity of the soil-plant-system. Therefore, after the disaster of Chernobyl, harvest and consumption of EMC fruiting bodies were restricted, or even directly forbidden, in contaminated sites (Dupré de Boulois et al, 2008).…”
Section: Introductionmentioning
confidence: 99%